QUALIDADE NO ATENDIMENTO COMO FATOR DE COMPETITIVIDADE: ESTUDO REALIZADO EM UMA MICROEMPRESA FAMILIAR DO RAMO DE CONFECÇÕES DE LUPIONÓPOLIS-PR - Thais Rubia Ferreira Lepre; Érica Aparecida do Nascimento Crão; Sandra Severiano Moreira (Universidade do Oeste Paulista, 2016)
With a constantly changing market, and increasingly competitive, to keep the family microenterprises need to achieve excellence in service, as compete with large organizations, a differential is to offer quality service, in order to retain the customers and still stand out from competitors. So this research is very important for any family microenterprises, contributing valuable information in the difficult customer loyalty path. It also will benefit microentrepreneurs, helping them to understand that good service can be a competitive advantage, able to leverage their sales. Thus, the objective of this research lies in analyzing the current state of care of a family microenterprise, the garment branch, located in the city of Lupionópolis-PR and propose ways to make it more competitive by improving customer relations. As for methodology, the survey was conducted through qualitative approach, and the case study method as a driver and literature, combined with questionnaire and interview as data collection instrument. It was found with this analysis, the database implementation, post-sales, and training within the company is able to improve the relationship with customers, causing the company to obtain excellence in service, making it more competitive.